2023
DOI: 10.1101/2023.02.21.529403
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fetal liver macrophages contribute to the hematopoietic stem cell niche by controlling granulopoiesis

Abstract: During embryogenesis, the fetal liver becomes the main hematopoietic organ, where stem and progenitor cells as well as immature and mature immune cells form an intricate cellular network. Hematopoietic stem cells (HSCs) reside in a specialized niche, which is essential for their proliferation and differentiation. However, the cellular and molecular determinants contributing to this fetal HSC niche remain largely unknown. Macrophages are the first differentiated hematopoietic cells found in the developing liver… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…For a long time, the FL was thought to be an intermediate reservoir for HSC expansion after their initial generation in the AGM, in preparation to their lifelong residency in the BM. Several recent work revolutionized this concept and showed that FL is in fact a complex hub in which distinct waves of progenitors differentiate, expand and might even mature with mechanisms still largely unknown 33,34,38,63,[79][80][81] . Indeed, ours and others' data imply that fetalrestricted HSPC and adult-type HSCs coexist in the FL, where they undergo different processes leading respectively to differentiation and self-renewal.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time, the FL was thought to be an intermediate reservoir for HSC expansion after their initial generation in the AGM, in preparation to their lifelong residency in the BM. Several recent work revolutionized this concept and showed that FL is in fact a complex hub in which distinct waves of progenitors differentiate, expand and might even mature with mechanisms still largely unknown 33,34,38,63,[79][80][81] . Indeed, ours and others' data imply that fetalrestricted HSPC and adult-type HSCs coexist in the FL, where they undergo different processes leading respectively to differentiation and self-renewal.…”
Section: Discussionmentioning
confidence: 99%